INTERNET USERS AND MACROECONOMIC FACTORS' IMPACT ON INDONESIA-MALAYSIA ISLAMIC FINANCE INDEX - Milhatun Nisa'; Muhammad Ismail Sunni (Universitas Airlangga, 2024)
Introduction: The rise of the internet has revolutionized the way businesses operate and people interact globally, without exception, including Islamic finance. This paper aims to investigate whether or not the level of internet users, GDP per capita, exchange rate, labor force, and poverty are the determinants of the increase of the Islamic Finance Index (IFI) in Indonesia and Malaysia. Methods: This research is a quantitative study that employs a balance panel regression and causality tests for the period 2013 to 2020 quarterly. Results: It is empirically found that there was a relationship between internet users and other macroeconomic variables on IFI in the long term, which was significant. However, only the labor force and exchange rate have significantly and negatively impacted IFI. While the remaining variables were expected to be positive, poverty uniquely did not contribute to the performance of Islamic finance. Furthermore, the empirical findings portrayed that all determinants influenced the endogenous variable, but not the contrary. Conclusion and suggestion: By analyzing and delving into the link between internet users, macroeocnomic factors and Islamic finance, this study fills the literature gap which will be a guide for both policymakers and academies to grasp what dominant variables to prioritize for the acceleration of Islamic finance rectification in both Indonesia and Malaysia, aligned with the increasing rate and impact of internet users.